An Interview with David Henry Hwang. Issue 2 (13th April 2016) - Young, Harvey
Abstract : Since winning wide acclaim and a Tony Award for his play M. Butterfly in 1988, David Henry Hwang (Fig. 1) has remained one of the brightest luminaries in American theatre. A playwright, screenwriter, and librettist, he regularly tells stories that center on complex characters and reveal their experiences with Western imperialism, American racism, and cross-generational family differences. His works include the plays FOB, Golden Child, Yellow Face, Chinglish, and Kung Fu ; the revised book for the 2002 Broadway revival of the Rodgers and Hammerstein's musical Flower Drum Song ; and, most recently, episodes of the television series The Affair . In this interview, Hwang reflects on the longevity of East West Players, comments on today's culture wars, and shares his perspective on the current state of Asian American theatre.